Literary Land Claims : The "Indian Land Question" from Pontiac's War to Attawapiskat - Fee, Margery, 1948- (Book collections on Project MUSE., 2015)
"Margery Fee examines John Richardson's novels about Pontiac's War and the War of 1812 that document the breaking of British promises to Indigenous nations. She provides a close reading of Louis Riel's addresses to the court at the end of his trial in 1885, showing that his vision for sharing the land derives from the Indigenous value of respect. Fee argues that both Grey Owl and E. Pauline Johnson's visions are obscured by challenges to their authenticity. Finally, she shows how storyteller Harry Robinson uses a contemporary Okanagan framework to explain how white refusal to share the land meant that Coyote himself had to make a deal with the King of England."--Publisher